PENGARUH METODE DEMONSTRASI BERBANTU MEDIA WAYANG KARTUN TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS II SDN PANDEAN LAMPER 01 SEMARANG - Aisatul Munawarah; Sutrisno Sutrisno; Diana Endah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Backgrounds encourage research this is the students under kkm obtained from 36 students as many as 9 students who were eligible a score of above criteria minimal ( kkm the 68 , while the rest is 27 students value under kkm.It is also because the learning teachers not maximum uses the learning creative and innovative.Problems this research is how the influence of a method of a demonstration with puppet cartoonsmedia of the results of study Indonesian Language to their students class IISDN Pandean Lamper 01 Semarang?.The purpose of this study is to find the influence of a method of a demonstration puppet cartoonsmedia of the results of students learn his class II SDN Pandean Lamper 01 Semarang.The kind of research this is research quantitative the form of pre-eksperimental design to a draft one-group pretest-posttest design.Population this research is all students class II SDN Pandean Lamper 01 Semarang years lessons 2016 / 2017. Samples to be taken is all students class II with using a technique nonprobability sampling shaped sampling saturated.The analysis of skill his students who calculated use of uji-t by the number of = 36 students with an average pretest = 59,81 and posttest = 77,35 known based on the calculation of obtained t-count of 7.15 while t-tabel 1,71 with db n-1 = 36-1 = 35, with the economic situation of significant 0.05 of 1,71 because t-count > t-tabel namely 7.15 > 1,71 so H0 were rejected and Ha accepted.So that it can be said that method demonstration with puppet cartoonsmedia influential of the results of study Indonesian Language to their students class II SDN Pandean Lamper 01 Semarang.Then the researcher convey suggestions to make a method of a demonstration with puppet cartoonsmedia could still applied to learning, because this method can create learning fun.